Decorative and applied art in museum and excursion work with future teachers of fine arts - O. Smyrnova (Academy of Cognitive and Natural Sciences, 2009)
The article is devoted to actuality of the decoratively-applied art in mueum-excursim work with the future teachers of fine art.